Handbuch Feministische Perspektiven auf Elternschaft - Haller, Lisa Yashodhara Dr; Schrupp, Antje Dr; Wolf, Katharina; Herz-Jakoby, Alia; Lange, Katrin; Tretau, Alisa; Spahn, Annika; Derboven, Wibke; Cammarata, Patricia; Schopp, Nikola; Charles, Perla; König, Jochen; et al. (Verlag Barbara Budrich, 2022)
Parenthood: A neglected perspective in feminist debates?For a long time, feminist debates hardly dealt with parenthood and family. The equality feminism that has set the tone up to the present is oriented toward equality with men.men - unbound and freed from care work by women. Timeschange: a shift in the perspective on parenthood is making its way into feminist debates and struggles. No longer directed against the family, but against conditionsin which life with children becomes an imposition.The handbook brings together 50 voices of feminism on the subject of parenthood.The contributions use buzzwords to explore the question,how motherhood, fatherhood and parenthood are processed in different feminist currents. How are legalaspects of the exercise of motherhood and fatherhood interpreted? Whatpaths lead to parenthood? And what do feminist utopias of a goodof a good life with children?